VPIV PRIČAKOVA J A USPEŠ OST (Filološke studije, 2019)
The classical study of Pygmalion effect was conducted in 1968 by Rosentahl and Jacobson on elementary school children. They find that teacher expectations can act as self-fulfilling prophecies because students' achievements come to reflect the expectations. Pygmalion studies were also undertaken on nonschool organizations. In the work organizations it was found that people perform better when a leader has high expectations on them and shows confidence in them. Awareness and nonawarenes determinants of Pygmalion effect will be explained as well. Pygmalion Leadership Style and internal-external efficacy model will be presented. This model distinguishes between general and specific self-efficacy and between self-efficacy and collective efficacy. Beside Pygmalion effect the Galatea effect will also be presented, where self-produced expectations influence individuals whose own self-expectations have been raised. The negative impact of low teacher expectations on performance is colled Golem effect.